2022
DOI: 10.1002/prot.26301
|View full text |Cite
|
Sign up to set email alerts
|

The amyloid concentric β‐barrel hypothesis: Models of amyloid beta 42 oligomers and annular protofibrils

Abstract: Amyloid beta (Aβ) peptides are a major contributor to Alzheimer's disease. They occur in differing lengths, each of which forms a multitude of assembly types. The most toxic soluble oligomers are formed by Aβ42; some of which have antiparallel β‐sheets. Previously, our group proposed molecular models of Aβ42 hexamers in which the C‐terminus third of the peptide (S3) forms an antiparallel 6‐stranded β‐barrel that is surrounded by an antiparallel barrel formed by the more polar N‐terminus (S1) and middle (S2) po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…A β 42 β PFO models may differ in structure and permeation mechanism depending on the respective oligomer size distribution. Previously suggested pore models ( 17 , 36 , 50 , 62 , 63 ) do not feature exposed transmembrane β -sheet edges and often lack the N-terminal domain altogether ( 30 , 36 , 50 ). Ion channel–like A β 42 structures with inner pores that are sufficiently stable and wide to conduct solvated ions would likely require folding into highly regular and long transmembrane β -barrels ( 62 , 63 ) or formation of much larger, high molecular-weight assemblies with annular or concentric pores ( 50 , 63 ).…”
Section: Discussionmentioning
confidence: 98%
“…A β 42 β PFO models may differ in structure and permeation mechanism depending on the respective oligomer size distribution. Previously suggested pore models ( 17 , 36 , 50 , 62 , 63 ) do not feature exposed transmembrane β -sheet edges and often lack the N-terminal domain altogether ( 30 , 36 , 50 ). Ion channel–like A β 42 structures with inner pores that are sufficiently stable and wide to conduct solvated ions would likely require folding into highly regular and long transmembrane β -barrels ( 62 , 63 ) or formation of much larger, high molecular-weight assemblies with annular or concentric pores ( 50 , 63 ).…”
Section: Discussionmentioning
confidence: 98%
“…22 Overall, a wide range of concentric β-barrels is consistent with image-averaged electron micrographs. 23 Inspired by many biological ion channels using α-helix bundles, simulations showed that the trimer and tetramer of Aβ17−42 transmembrane α-helices are possible candidates to conduct Na + ions. 24 Apart from the organization in α-helix bundles and β-barrels made of β-hairpins to build pores, Nussinov et al proposed, on the basis of atomic force microscopy (AFM) imaging and modeling, that the Aβ17−42 pentamer with a U-shaped fibrillar state is able to insert into the lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…The tetrameric topology comprises a six-stranded β-sheet core with the two external Aβ peptides forming β-hairpins . Overall, a wide range of concentric β-barrels is consistent with image-averaged electron micrographs …”
Section: Introductionmentioning
confidence: 99%
“…62 More recent work proposed concentric barrels for oligomers in solution. 63 Other models were based on the structure of the fibrils, 64−66 which, when subjected to MD simulations, broke up into distinct subunits. The insertion of such dimers and pentamers into the bilayer was also studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some are de novo constructions based on intuition and experimental constraints. , An elaborate and unusual 36-mer transmembrane structure with concentric barrels was found stable in short molecular dynamics (MD) simulations . More recent work proposed concentric barrels for oligomers in solution . Other models were based on the structure of the fibrils, which, when subjected to MD simulations, broke up into distinct subunits.…”
Section: Introductionmentioning
confidence: 99%